Transformasi Geometri Rotasi Citra Digital Untuk Mendapatkan Kompresi Optimal Menggunakan Metode Lossless Dan Lossy - Hastha Sunardi; Zulkifli Zulkifli; Fery Antony (Jurnal Informatika Global)
Data has a fairly important meaning, because it contains the information needed. Besides being important, the process of data exchange and storage certainly requires space and requires high costs. For this reason, data compression is an interesting topic for continuous research. The success of previous research in obtaining optimal compression, it will be more interesting, if tested on the Lossless and Lossy Compression Methods, which of the two methods results in more optimal compression. The amount of the compression ratio without the image rotation process. For regular images obtained Huffman Compression Ratio 48.7076% and Wavelet Compression 47.3888%. If we compare the compression ratio by comparing the initial file size without playback compared with the final file size after 90 degrees of playback, the ratio is 61.03%. Meanwhile, for irregular images, a ratio of 49.79% was obtained at 180 degrees of image rotation. The results of compression, both without and with rotation, Wavelet Compression is more optimal than Huffman Compression. Keywords: Digital Image, Test Image, Lossless, Lossy, Huffmann Algorithm, Haar Wavelet